2020
DOI: 10.14202/vetworld.2020.1410-1416
|View full text |Cite
|
Sign up to set email alerts
|

Detection and antibiotic resistance of Mycoplasma gallisepticum and Mycoplasma synoviae among chicken flocks in Egypt

Abstract: Background and Aim: Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) are the most significant pathogens of avian mycoplasmosis. This study aimed to isolate and identify MG and MS from chickens and detect the various virulence genes in the isolates. Moreover, the efficacies of different antibiotics were tested to identify suitable treatment regimens. Materials and Methods: We isolated MG and MS from 487 chicken samples of different ages located in different Governorates in Egypt using conventional is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
3
21
1
1
Order By: Relevance
“…The incidence profiles of the study, as mentioned in the results, is closely nearly to the conclusion of Bharathi et al. (2018) , Erfan and Marouf (2019) , Emam et al. (2020) , Marouf et al.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The incidence profiles of the study, as mentioned in the results, is closely nearly to the conclusion of Bharathi et al. (2018) , Erfan and Marouf (2019) , Emam et al. (2020) , Marouf et al.…”
Section: Discussionsupporting
confidence: 78%
“…From our results, the highest isolation percentage was 83% from infraorbital sinus aspirates, 79.4% from lung, 72% from air sacs, 67.4% from tracheal bifurcation, 40% from litter samples and 29.4% from tracheal swabs. Also, Mohamed (1997) , Reda and El-Samie (2012) , Emam et al. (2020) showed that the highest isolation percentage was from air sacs as 15.7, 23.3, and 21.5%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, the PK/PD findings demonstrated that the AUC 24h /MIC had the best correlation with the anti-mycoplasmal activity (correlation coefficient (R 2 ) = 0.9628). In accordance with that of Emam et al [ 55 ], the MIC of spiramycin against M. synoviae strain (MS WVU-1853) was estimated to be 0.0625 µg/mL. On the basis of this MIC, the obtained AUC 24h /MIC for mycoplasmacidal activity (185 h), the evaluated unbound portion of spiramycin in chicken plasma (65.4%), and the oral bioavailability (77.1%), the appropriate daily dosage of spiramycin needed to achieve a mycoplasmacidal effect (2 log 10 decline in the Mycoplasma count) against M. synoviae in chickens was calculated to be 15.6 mg/kg/day.…”
Section: Discussionsupporting
confidence: 91%
“…For in depth study of M. gallisepticum in a specific region to understand the epidemiological niche, transmission of diseases and finding of new track of outbreaks, there is need to adopt a most reliable technique for differentiation the specie in more detail (Loolmani et al, 2014). The mgc2 gene targeted in this study is most specific, and sensitive and can be used as reference only for molecular based identification of M. gallisepticum (Youni et al, 2018;Emam et al, 2020). The particle sequencing and analysis of mgc2 gene showed a 100 percent similarity of local isolates from this study with isolated reported from India.…”
Section: Discussionmentioning
confidence: 64%